Eimeria ferreirai n. sp. (Chromista: Miozoa: Eimeriidae) from doves Leptotila spp. (Columbiformes: Columbidae) from Brazil - Oliveira, Mariana S.; Genovez-Oliveira, Jhon Lennon; Ortúzar-Ferreira, Carlos Nei; Maronezi, Carla; Thode-Filho, Sergio; Cardozo, Sergian V.; Oliveira, Águida A.; Lima, Viviane M.; Berto, Bruno P. (Zootaxa, 2020)
The doves and pigeons constitute a taxonomic group (Columbiformes: Columbidae) of granivorous and frugivorous birds with a worldwide distribution. The current work aims to describe morphologically and molecularly a new protozoan from white-tipped doves Leptotila verreauxi Bonaparte, 1855 and grey-fronted doves Leptotila rufaxilla (Richard & Bernard, 1792) in Southeastern Brazil. Eimeria ferreirai n. sp. has oocysts that are sub-spherical to ellipsoidal, 21.4 × 18.8 μm, with smooth, bilayered wall, ~1.6 μm thick. Micropyle present. Oocyst residuum absent, but one to two polar granules are present. Sporocysts are elongate ovoidal to boomerang-shaped, 13.4 × 6.9 μm. Stieda body triangular to lozengal. Sporocyst residuum is composed of granules of different sizes. Sporozoites are vermiform with refractile body and nucleus. Sequencing of the mitochondrial cytochrome c oxidase subunit 1 (COI) gene and the subsequent phylogenetic molecular comparisons supported the description of the new species, since the maximum similarity was 90-95% with eimeriid species of Columbiformes, Anseriformes, Galliformes and Passeriformes. Thus, this is the first coccidian species reported from Leptotila spp. and the twentieth description of an eimerian from Columbiformes in the World.